The Model Of Physics Experiments Using Smartphone Sensors In Senior High School 1 Pangkalpinang - Rediansyah, Herfien (SEAQIS Journal of Science Education, 2022)
The aim of this research is to develop a model physics experiment manual in high school by utilizing sensors on smartphones as a source of observing data on physics experiments to increase students' level of understanding. The research method used is research and development. The teacher arranges physics experiments manual so that students can use it. Retrieval of data in the experiments uses the Research Based Learning (RBL) method so that students get the freedom to be creative using smartphone sensors.The results of the study are expected to help students understand the concepts of physics through experiments data using smartphone sensors